Land Procurement for Public Interest Against Destroyed Land: Natural Events and Legal Certainty - Embun Sari; Muhammad Yamin; Hasim Purba; Rosnidar Sembiring (Salehan Institute of Higher Education, 2022)
Based on a case study on the construction of the Semarang-Demak Toll Road, this study aims to investigate and investigate land acquisition for the public interest for land that has been destroyed as a result of natural events and its legal certainty. The research method used is socio-legal with primary data in identification, field measurements, and other supporting data. Semarang-Demak Toll Road property acquisition demonstrated tidal inundation on the north shore. Subsidence exacerbates Semarang's flooding. On flooded land, sea dikes and retention ponds prevent tidal floods. If just for transportation, the Semarang-Demak Toll Road can be built in flood-free areas or over the sea, like Bali's Mandra Toll Road. Land acquisition concerns delayed the Semarang-Demak Toll Road. Lack of land limitations has delayed land purchases. In the Semarang-Demak Toll Road land acquisition, destroyed land is not a problem under Indonesian law. 2021's Regulation 18 defines destroyed land. Destroyed land will drive people to take better care of their land and be more concerned about global warming or land subsidence. The state honors the landowner's emotional connection by paying for spiritual care. Doi: 10.28991/CEJ-2022-08-06-06 Full Text: PDF